Produksi Nata de Whey: Solusi Penanganan Limbah Keju dari PT. Mazaraat Lokanatura Indonesia dan Pemberdayaan Masyarakat - Siti Lusi Arum Sari; Pangastuti Artini; Setyaningsih Ratna; Susilowati Ari; Purwoko Tjahjadi; Muhammad Fajar Permana (Universitas Sebelas Maret, 2025)
Nata de Whey Production: Solutions for Handling Cheese Waste from PT. Mazaraat Lokanatura Indonesia and Community Empowerment. One of the problems faced by PT Mazaraat Lokanatura Indonesia is the abundant liquid cheese waste (whey). If not properly managed, cheese whey could be harmful to the environment. Whey still contains a lot of milk nutrients so it can be used as a substrate for the production of nata de whey. Based on this, the purpose of this activity was to produced nata de whey from which was served as a nata-salak cocktail. This activity involves 2 partners, namely PT Mazaraat Lokanatura Indonesia and the Tegalrandu community, Srumbung, Magelang. The activity was carried out in an integrated manner with the KKN MBKM Biology Study Program, FMIPA UNS in Tegalrandu, Srumbung, Magelang. The stages of the activity were: socialization, provision of KKN students, training in making nata and cocktails, and mentoring. Training starts from whey preparation, fermentation, processing nata into cocktails, and packaging. Mentoring and monitoring activities were carried out directly by the KKN student group. Socialization and FGD with PT Mazaraat were held on June 26, 2023. Through this FGD, the management of PT. Mazaraat supports the use of whey by the community. Socialization with the Tegalrandu community were carried out in an integrated manner with the implementation of the MBKM KKN program. Before the training, KKN students had practiced making Nata and cocktails. The Tegalrandu village community was very enthusiastic about participating in the training activities for making nata de whey and nata-salak cocktails. Through this activity, A nata-salak cocktail product that may be utilized as an unique and extraordinary Tegalrandu village product was created. This activity provides an alternative solution to the waste problem of PT Mazaraat Lokanatura and opens up business opportunities for the Tegalrandu, Srumbung, Magelang community.